Analysis of the Influence of Gamification Based Digital Learning Media on Students' Learning Interests Evolution - Rina Astuti; Putri Agustina; Lina Agustina (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effect of gamification based digital learning media on interest in learning evolution in increasing students' learning motivation. This study uses a quantitative quasi-experimental approach with a nonequivalent control group design. This study consists of three types of variables, gamification based digital learning media, interest in learning evolution, student characteristics. The study population and sample students in class XI IPA SMA Muhammadiyah 01  Surakarta. The results of the study showed a significant increase in learning interest in the experimental group compared to the control group. After being given certain treatments, the experimental group showed a much higher average posttest score, which was 85.13, while the control group only reached 71.45. This indicates that the treatment given to the experimental group succeeded in significantly increasing their learning interest. All indicators used to measure learning interest, such as attention, relevance, self-confidence, and satisfaction, also showed a higher increase in the experimental group. Research proves that digital technology and gamification mechanisms can effectively overcome learning challenges in abstract materials such as evolution. This makes a substantive contribution to building bridges between gamification theory, educational technology, and biology learning practices.